Postoperative Skin Complications after Spine Surgery in the Prone Position - Ali Baradaran Bagheri; Leila Sadati; Alireza Beyrami; Sajad Fatollahi; Zahra Nouri Khanegah; Hojjat Torkamandi (Golestan University Of Medical Sciences, 2019)
Background and objectives: One of the adverse effects of prone positioning in spine surgery is the occurrence of skin damage. Due to the high rate of spine surgeries and the frequent use of prone positioning during these procedures, we aimed to investigate postoperative skin complications after spine surgery in the prone position. Methods: This descriptive cross-sectional study was performed in 2016-2017 on 160 patients undergoing spine surgery in the prone position at a teaching hospital in Tehran, Iran. The patients' body parts were examined for presence any redness, ecchymosis and pressure ulcers before discharge from the hospital. Collected data were analyzed in SPSS software (version 19) using descriptive statistics, Chi-square test, Mann-Whitney U test and Kendall's correlation coefficient. Results: Almost all patients had skin damage, especially redness, in the postoperative stage. Age, gender, duration of surgery, height, weight and body mass index were significantly associated with incidence of skin damage (P<0.05). Conclusion: Our results indicated that the incidence of postoperative skin damage is relatively high in patients undergoing spine surgery in the prone position. Therefore, it is recommended to take appropriate precautions in order to prevent these complications.